LANDSCAPE COMPOSITION IN VISUAL ARTS - Chori Kholmurodovich Sadatov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the role of art therapy in the educational process of higher education institutions, particularly in visual arts classes. The main methods of art therapy, their impact on students’ emotional well-being, the development of creative abilities, and the formation of professional competencies are highlighted. The article also analyzes the results of applying art-therapeutic approaches in educational practice.